From import substitution to export diversification in Colombia - Jan Peter Wogart (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1975)
The recent surge of industrial exports from some Latin American countries has prompted a number of studies which have examined the new outward-looking strategies of a few nations such as Brazil, Mexico and Argentina. There are, however, at least two characteristics which do not apply to most other countries of the Southern Hemisphere of the Americas. First, export diversification in the large nation states began only after import substitution had run its course and seemed to be exhausted. Secondly, in spite of their importance for the balance of payments, exports contribute a relatively small part to the formation of the gross national products in these countries. Hence industrialization will depend on the expansion of domestic markets. This situation is already quite different in the Andean countries, where import substitution industrialization was not only hampered by small and fragmented markets but also by lower per capita income and more widespread poverty. To overcome this handicap Chile, Bolivia, Peru, Ecuador, Colombia and later Venezuela have joined in the Andean Common Market. Simultaneously they have promoted industrial exports the results of which have been modest except in the case of Colombia. Unless one includes Peru's fishmeal into industrial exports, only Chile and Colombia have been able to raise the share of manufactured goods in total exports beyond 10 %. But whereas industrial exports' share has been falling considerably in Chile in the last few years, Colombia was able to raise that share from less than 2 % in 1960 to over 15 % in 1973.
Keywords: 330